'Devenir compositeur': Notes on the Insertion of Argentine Composers in the Contemporary French Music Scene (1970–2000). Issue 3 (October 2020) - LIUT, MARTIN
Abstract: This article studies a group of nineteen Argentinean composers who settled in Paris between 1970 and 2000. In addition to social and political factors of Argentine history – including the last military dictatorship (1976–83) and the 1989 period of 'hyperinflation' (1989) – these composers wanted to develop their careers in a professional field with the history, size, and diversity of Paris. Since the 1970s, France began a strong state policy supporting the arts; this action promoted a process of internationalization of Paris's artistic life. Contemporary music was viewed by participants and creators as an open and cosmopolitan space. Although the paradigm of autonomy suggests that nationality is less relevant than the individuality of each composer, the latter continues to function as an identity marker and, therefore, as a classification strategy both in France and in Argentina.